Empowering Marketing, Financial, and Operational Aspects of Micro-Sized Entrepreneurship with Business Canvas Approach: The Case Study of Sweet Potatoes Crackers Business of Mrs Atim (Ubi Kremes Ibu Atim) in Sukatani, Cianjur, West Java - Desmonda Theodora; Albert Hasudungan; Stephanie Djohan; Augustinus Abdurrahman; Leonard Rozalie; Pandu Dwi Putranto (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
The aim of this case study was to explore micro-scale business problems and their solutions of the micro-scale business Sweet potato crackers owned by Mrs Atim (Ubi Kremes Ubi Ibu Atim) in Sukatani, Cianjur, West Java. A wide range of economic activities of micro, small, and medium enterprises (MSMEs) have contributed significantly to nurture entrepreneurship in Indonesia. Nonetheless, some MSME entrepreneurs have lack capacity to manage their business professionally. In this case study, the micro-scale entrepreneurs learn and do business by selftaught. According to the business canvas approach, the obstacles to managing their business lays in their underdeveloped marketing, book-keeping, and operational business aspects. The business canvas approach identifies matches and mismatches between business resources and products. We have conducted direct observations and interviews through personal interactions with the business actors for six months. Specifically, through the community services held by Universitas Prasetiya Mulya, we have to formulate business actors' business improvement actions, particularly on more well-structured administrative book-keeping, more diversified marketing promotions, and establish sound business operational procedures to efficacy their resources. To community development contribution, it was found that capacity building was a significant factor to deliberate, especially to that micro-business that aimed to grow in their limited entrepreneurship skills.